Avoiding Negative Impacts from Urban Morphology: Case study of the “Neighbourhood Unit” - Mehaffy, Michael West; Porta, Sergio; Romice, Ombretta (A+BE | Architecture and the Built Environment, 2015)
A design decision support model must not only account for elements of urban form that help to reduce per-capita GHG emissions, it must also account for elements of urban form that work to increase those emissions. This chapter examines the case study of a very prevalent urban design model, the so-called “neighbourhood unit”, and evaluates its impact on urban form as well as emissions.